Noise Reduction System Using Passive Bandpass Noise Filter on Podcast Microphone - Fadlan Siregar, Muhammad; Satria, Habib; Irwanto Misrun, Muhammad; Salam, Rudi (LPPM Universitas Andalas, 2024)
The general properties of waves are refraction, reflection, bending (diffraction), interference and polarization. Sound is a form of wave and is in accordance with the law of wave refraction where waves coming from a less dense medium to a denser medium will be refracted closer to the normal line or vice versa. Sound waves easily experience diffraction because sound waves in air have wavelengths of around several centimeters to several meters. Then basically every room, whether you feel it or not, will always have sound. This is inversely proportional to light which has a wavelength of around 500 mm. Therefore, an interference reduction system using a passive bandpass interference filter on the podcast microphone is necessary to reduce interference. Test results carried out by filters used to reduce noise using Passive Band Pass. the waveform is still the original spectrum at 0 Hz – 120 Hz, the original sound conditions and does not cause interference, but interference occurs and filtering Category (Noise %) 10 – 40 low - 98 – 99 high.